Blue Sukuk dan Kontribusinya Terhadap Keberlangsungan Ekosistem Laut di Indonesia - Imroatus Sholiha; Hasanah, Mifatahul; Oktaviani, Lusi (Universitas Muhammadiyah Jember, 2023)
Indonesia is a maritime country where most of the people are fishermen. Indonesia also has potential seas, but due to unstructured management, poverty still plagues the people around the seas. The blue economy is promoted to protect marine ecosystems from damage and for the welfare of coastal communities. The blue economy needs to be supported by sharia financial instruments for funding so that the blue economy is realized properly, these instruments can use blue sukuk. This study aims to examine how blue sukuk is applied in Indonesia as a basis for strengthening the economy of coastal communities. This study uses literature research by seeking information from several related literatures and is presented qualitatively. The results found that if blue sukuk is issued it will encourage the blue economy program that has been launched by the government, especially for strengthening coastal communities. 1.3 million people in coastal communities are still below the poverty line. The management and protection of marine ecosystems need to be encouraged and there needs to be a supporting financial instrument that can use blue sukuk.